A high modulus asphalt structural material and its preparation process

By introducing reinforcing epoxy resin, high modulus agent and wear-resistant aggregate into asphalt structural materials, a high-density cross-linked network and reasonable gradation are formed, which solves the problems of low modulus, poor wear resistance and poor resistance to high and low temperatures of traditional asphalt structural materials, and improves the wear resistance and rutting resistance of high modulus asphalt structural materials.

CN118702438BActive Publication Date: 2025-02-14ZHONGYIFENG (SUZHOU) MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410695477.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-02-14
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

Traditional asphalt structural materials have low modulus, poor wear resistance, and are not resistant to high and low temperatures, which affects their rutting resistance and service life.

Method used

High-modulus asphalt structural material is prepared by combining reinforced epoxy resin, high-modulus agent and wear-resistant aggregate through a specific process. The reinforced epoxy resin is formed by the reaction of carbon fiber, epoxy resin and catalyst to generate a high-density cross-linked network. The high-modulus agent improves the stability of the material through blending and irradiation treatment. The wear-resistant aggregate is formed by mixing refractory materials of different particle sizes to form a reasonable gradation.

Benefits of technology

It significantly improves the high and low temperature resistance, wear resistance and rutting resistance of asphalt structural materials, extends the service life of pavement and enhances mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004869580470000031
    Figure BDA0004869580470000031
  • Figure BDA0004869580470000121
    Figure BDA0004869580470000121
Patent Text Reader

Abstract

The invention discloses a high modulus asphalt structural material and a preparation process thereof, belonging to the technical field of asphalt mixtures, and is used to solve the technical problems of low modulus, poor wear resistance and high and low temperature difference resistance of traditional asphalt structural materials. The invention comprises the following steps: heating the matrix asphalt at a constant temperature, adding a reinforcing epoxy resin, a high modulus agent and a wear-resistant aggregate, shearing and stirring to obtain the high modulus asphalt structural material. The invention further improves the high and low temperature resistance, rutting resistance and bending stiffness modulus of the prepared asphalt structural material by adding a carbon fiber reinforced epoxy resin system, a combination of coarse, medium and fine aggregates, copolymerization and irradiation of various polyolefins and modification with acrylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of asphalt mixtures, and in particular relates to a high modulus asphalt structural material and a preparation process thereof. Background Art

[0002] Asphalt pavement has received extensive attention in my country's highway construction field due to its excellent performance. Asphalt pavement has the characteristics of short construction period and easy maintenance. However, under the combined effect of factors such as growing traffic volume and heavy traffic, asphalt pavement is still facing huge challenges.

[0003] Rutting is the indentation left on the road surface by vehicles under the combined effects of vehicle load and climate. The existence of rutting seriously affects the driver's operability and comfort, and also affects the safe driving of the vehicle. High modulus asphalt structural materials can effectively reduce the occurrence of plastic deformation of the road surface, effectively inhibit the incidence of rutting diseases, and thus extend the service life of the road. At the same time, due to the special material composition of high modulus asphalt mixture, its fatigue resistance is significantly better than that of traditional dense asphalt mixture.

[0004] Patent application CN106673503A discloses a composite modified asphalt mixture for steel bridge deck and a preparation method thereof. The composite modified asphalt mixture includes wear-resistant aggregate, composite modified asphalt, limestone powder and wood cellulose. The wear-resistant aggregate is specifically basalt. However, it is still of positive significance to explore and select other inorganic minerals with different particle sizes to replace conventional wear-resistant aggregates to significantly improve the modulus and wear resistance of modified asphalt. In addition, the high and low temperature resistance and flexibility of the composite modified asphalt mixture are not good, which is not conducive to improving the anti-rutting performance of the asphalt mixture.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation process of a high modulus asphalt structural material, which is used to solve the problems of low modulus, poor wear resistance and low temperature resistance of traditional asphalt structural materials.

[0007] The purpose of the present invention can be achieved by the following technical scheme: A preparation process of a high modulus asphalt structural material, comprising the following steps:

[0008] 5-10 parts of base asphalt are heated at a constant temperature of 130-140°C until it becomes fluid. When the temperature is constant, 1-5 parts of reinforcing epoxy resin, 1-5 parts of high modulus agent and 70-80 parts of wear-resistant aggregate are added, and sheared and stirred to obtain a high modulus asphalt structural material.

[0009] The asphalt structural material prepared by the present invention includes base asphalt, reinforced epoxy resin, high modulus agent and wear-resistant aggregate. The reinforced epoxy resin, high modulus agent and wear-resistant aggregate as admixtures are helpful to improve the high and low temperature resistance, wear resistance and rutting resistance of the prepared asphalt structural material.

[0010] Furthermore, the reinforced epoxy resin system is prepared by the following steps:

[0011] The carbon fiber is ultrasonically dispersed in ethanol, and then dimethyl paraphenylene dimethyl cyanate and bisphenol A epoxy resin are added, and the mixture is stirred at 100 r / min at 60-70°C for 0.5-1h, and then a catalyst dibutyltin dilaurate is added, and the mixture is stirred evenly to obtain a mixed system, and the mixed system is heated to 110-120°C and kept warm for 1-2h to obtain a prepolymer, and the prepolymer is vacuum-foamed and vacuum-dried at 60-70°C to constant weight to obtain a reinforced epoxy resin system.

[0012] Under the action of organic tin catalyst, at a certain reaction temperature and reaction conditions, dimethyl para-xylene dimethyl cyanate and bisphenol A epoxy resin undergo epoxy ring-opening reaction, and the reaction principle is as follows:

[0013]

[0014] in,

[0015] When dimethyl para-xylene dimethyl cyanate and bisphenol A epoxy resin undergo copolymerization, various cyclic structures can be generated, which is beneficial to the formation of various cross-linked network structures, further improving the network structure density of the prepared enhanced epoxy resin system.

[0016] Furthermore, the usage ratio of carbon fiber, ethanol, dimethyl para-xylene dimethyl cyanate, bisphenol A epoxy resin and dibutyltin dilaurate is 10-20g:200mL:30-40g:30-50g:0.015-0.03g.

[0017] Furthermore, the preparation process of the high modulus agent comprises the following steps:

[0018] A1. Mixing ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene in a weight ratio of 1:1:1, adding the mixture to a banbury mixer for mixing, and obtaining a blend; adding the mixture to a twin-screw extruder for extrusion granulation, and obtaining a blended masterbatch; and irradiating the blended masterbatch with a high-energy electron accelerator, and obtaining an irradiated blended masterbatch;

[0019] Ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene are subjected to internal mixing and extrusion granulation to obtain a polymer alloy-blended masterbatch. When the blended masterbatch is irradiated with ultraviolet electron beams, the carbon-carbon single bonds, carbon-carbon double bonds, carboxyl groups and carbon-fluorine-fluorine groups on the main chains of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and tetrafluoroethylene molecules are easily broken, generating a large number of trapped free radicals, which further undergo cross-linking reactions and improve the overall stability of the blended masterbatch.

[0020] A2, acrylic acid and water are mixed to obtain a 20-30%wt acrylic acid aqueous solution; an emulsifier is added to the acrylic acid aqueous solution, and the mixture is stirred evenly to obtain an acrylic emulsion; the irradiated blended masterbatch and the acrylic emulsion are mixed, and then the mixture is heated to 80-90°C and reacted for 12 hours to obtain a modified blend; the modified blend is washed with ethanol and deionized water in turn, and then the modified blend is dried to a constant weight to obtain a high modulus agent.

[0021] Furthermore, in step A1, the speed of the internal mixer is 50-100r / min, the temperature of the internal mixer is 200-220°C, and the mixing time is 5-10min; the extrusion temperature of the twin-screw extruder is 160-180°C, and the extrusion time is 5min; the irradiation voltage is 0.5MeV, the irradiation beam density is 15-30mA, and the irradiation time is 10-20min.

[0022] Furthermore, in step A2, the emulsifier is SE-10, and the usage ratio of the acrylic acid aqueous solution and the emulsifier is 200mL:1-2mL; the weight ratio of the irradiated blended masterbatch and the acrylic emulsion is 1:20-30; and the drying temperature of the modified blend is 60-70°C.

[0023] Further, the wear-resistant aggregate is prepared by the following steps:

[0024] Siliceous and semi-siliceous refractory raw materials are mixed and ball-milled in a weight ratio of 1:1, and mixed and stirred at a high speed to obtain a coarse aggregate with a particle size of 20-30mm; basalt is ground to obtain a medium aggregate with a particle size of 10-20mm; carbide and nitride are mixed and ball-milled in a weight ratio of 1:1 to obtain a fine aggregate with a particle size of 3-5mm; the coarse aggregate, medium aggregate and fine aggregate are evenly mixed to obtain wear-resistant aggregate.

[0025] Aggregate is one of the important components of asphalt mixture. Suitable grading has a good effect on improving the low-temperature crack resistance and other properties of asphalt mixture. Siliceous and semi-siliceous refractory raw materials with a particle size of 20-30mm are used as coarse aggregate, basalt with a particle size of 10-20mm is used as medium aggregate, and a mixture of carbides and nitrides with a particle size of 3-5mm is used as fine aggregate. The above three raw materials with different particle sizes are evenly mixed to obtain wear-resistant aggregate.

[0026] Furthermore, the siliceous material is any one of silica, quartz sand, vein quartz or fused quartz, and their combinations; the semi-siliceous material is any one of pyrophyllite, diatomaceous earth or silicon micropowder, and their combinations; the carbide is any one of silicon carbide, boron carbide, and titanium carbide, and their combinations; the nitride is any one of silicon nitride, aluminum nitride, and boron nitride, and their combinations.

[0027] As another aspect of the present invention, a high modulus asphalt structural material is prepared by using a high modulus asphalt structural material preparation process.

[0028] The present invention has the following beneficial effects:

[0029] 1. Dimethyl para-xylene dimethyl cyanate has good heat resistance. Dimethyl para-xylene dimethyl cyanate and bisphenol A epoxy resin copolymerization can generate a variety of ring structures, and prepare epoxy resin systems with different cross-linking relationships. The composite epoxy resin system has a high-density cross-linking network to improve its modulus, mechanical properties and high temperature resistance. Carbon fiber is then used as a reinforcing phase to further improve the relevant properties of the composite resin, thereby obtaining a reinforced epoxy resin system.

[0030] 2. Ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene can improve the high temperature resistance of asphalt pavement, enhance the ability of pavement to resist rutting deformation, and extend the service life of pavement. The above substances are subjected to the mixing and co-mixing extrusion process to prepare the blended masterbatch, which can improve the compatibility, mechanical properties and thermal properties between the various material components, so that the performance of the various components of the blended masterbatch is complementary; the blended masterbatch is subjected to ultraviolet irradiation, and the main chain and side chain functional groups are broken to form active free radicals, which further induce a cross-linking reaction to obtain the irradiated blended masterbatch. The molecular structure of the irradiated blended masterbatch is transformed from a linear structure to a three-dimensional network structure, which further improves the mechanical properties and impact resistance of the blended masterbatch. The active free radicals obtained by ultraviolet irradiation are further used to induce the graft polymerization reaction of acrylic acid, enrich the functional groups on the surface of the prepared high modulus agent, which is beneficial to the chemical adsorption of the high modulus agent and other components of the asphalt structural material such as the enhanced epoxy resin system and wear-resistant aggregate, and further improves the modulus of the asphalt structural material.

[0031] 3. Silicon carbide, boron carbide and titanium carbide as carbides are all commonly used non-oxide refractory raw materials in the field of refractory materials. In nitrides, silicon, boron, titanium and nitrogen are bonded by strong covalent bonds, so nitrides have the advantages of high hardness, high melting point and stable structure. A mixture of carbides and nitrides with a particle size of 3-5 mm is used as fine aggregate, basalt with a particle size of 10-20 mm is used as fine aggregate, and a mixture of siliceous and semi-siliceous refractory raw materials is used as coarse aggregate. The gradation of coarse, medium and fine aggregates is more reasonable, which is beneficial to improving the mechanical properties, wear resistance, water damage resistance and high-temperature stability of the prepared asphalt structural material. The present invention adds reinforced epoxy resin, high modulus agent and wear-resistant aggregate to the matrix asphalt. The above components use functional groups to absorb and react with each other to form a stable whole. Each component helps to improve the high and low temperature resistance, wear resistance and rutting resistance of the prepared asphalt structural material. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] This embodiment provides a preparation process of a reinforced epoxy resin system, comprising the following steps:

[0035] 10 g of carbon fiber was ultrasonically dispersed in 200 mL of ethanol, and then added into a three-necked flask; 30 g of dimethyl paraben dicyanate and 30 g of bisphenol A epoxy resin were weighed and added into the above three-necked flask, mixed and stirred at 70°C at 100 r / min for 0.5 h, and then 0.015 g of catalyst dibutyltin dilaurate was added, and mixed and stirred evenly to obtain a mixed system; the three-necked flask was then heated to 110°C and kept warm for reaction for 1 h to obtain a prepolymer; the prepolymer was placed in a vacuum drying oven for vacuum bubbling, and then vacuum dried at 60°C to constant weight to obtain a reinforced epoxy resin system.

[0036] Example 2

[0037] This embodiment provides a preparation process of a reinforced epoxy resin system, comprising the following steps:

[0038] 15 g of carbon fiber was ultrasonically dispersed in 200 mL of ethanol, and then added into a three-necked flask; 35 g of dimethyl paraben dicyanate and 40 g of bisphenol A epoxy resin were weighed and added into the above three-necked flask, mixed and stirred at 65° C. at 100 r / min for 0.8 h, and then 0.02 g of catalyst dibutyltin dilaurate was added, and mixed and stirred evenly; the three-necked flask was heated to 115° C. and kept warm for 1.6 h to obtain a prepolymer; the prepolymer was placed in a vacuum drying oven for vacuum bubbling, and then vacuum dried at 68° C. to constant weight to obtain a reinforced epoxy resin system.

[0039] Example 3

[0040] This embodiment provides a preparation process of a reinforced epoxy resin system, comprising the following steps:

[0041] 20 g of carbon fiber was ultrasonically dispersed in 200 mL of ethanol, and then added into a three-necked flask; 40 g of dimethyl paraben dimethyl cyanate and 50 g of bisphenol A epoxy resin were weighed and added into the above three-necked flask, mixed and stirred at 100 r / min at 60° C. for 0.5 h, and then 0.03 g of catalyst dibutyltin dilaurate was added, and mixed and stirred evenly; the three-necked flask was heated to 120° C. and kept warm for 2 h to obtain a prepolymer; the prepolymer was placed in a vacuum drying oven for vacuum bubbling, and then vacuum dried at 70° C. to constant weight to obtain a reinforced epoxy resin system.

[0042] Example 4

[0043] This embodiment provides a preparation process of a high modulus agent, comprising the following steps:

[0044] A1. Ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene are mixed in a weight ratio of 1:1:1, and added to an internal mixer for internal mixing to obtain a blend; the internal mixer speed is 50r / min, the internal mixer temperature is 200°C, and the internal mixing time is 5min. The blend is added to a twin-screw extruder for extrusion granulation to obtain a blended masterbatch; the extrusion temperature is 160°C, and the extrusion time is 5min. The blended masterbatch is irradiated by a high-energy electron accelerator to obtain an irradiated blended masterbatch; wherein the irradiation voltage is 0.5MeV, the irradiation beam current density is 15mA, and the irradiation time is 10min.

[0045] A2. Mix acrylic acid and water to obtain a 20%wt acrylic acid aqueous solution; add 1mL of emulsifier SE-10 to 200mL of the acrylic acid aqueous solution, mix and stir evenly to obtain an acrylic emulsion; mix the irradiated blending masterbatch and the acrylic emulsion in a weight ratio of 1:20, then heat to 80°C and react for 12h to obtain a modified blend; then wash the modified blend with ethanol and deionized water in turn, and then add the modified blend to a 60°C oven and dry to constant weight to obtain a high modulus agent.

[0046] Example 5

[0047] This embodiment provides a preparation process of a high modulus agent, comprising the following steps:

[0048] A1. Ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene are mixed in a weight ratio of 1:1:1, and added to an internal mixer for internal mixing to obtain a blend; the internal mixer speed is 80r / min, the internal mixer temperature is 210°C, and the internal mixing time is 8min. The blend is added to a twin-screw extruder for extrusion granulation to obtain a blended masterbatch; the extrusion temperature is 170°C and the extrusion time is 5min. The blended masterbatch is irradiated by a high-energy electron accelerator to obtain an irradiated blended masterbatch; wherein the irradiation voltage is 0.5MeV, the irradiation beam current density is 20mA, and the irradiation time is 15min.

[0049] A2. Mix acrylic acid and water to obtain a 25%wt acrylic acid aqueous solution; add 1.5mL of emulsifier SE-10 to 200mL of the acrylic acid aqueous solution, mix and stir evenly to obtain an acrylic emulsion; mix the irradiated blending masterbatch and the acrylic emulsion in a weight ratio of 1:24, then heat to 86°C and react for 12h to obtain a modified blend; then wash the modified blend with ethanol and deionized water in turn, and then add the modified blend to a 66°C oven and dry to constant weight to obtain a high modulus agent.

[0050] Example 6

[0051] This embodiment provides a preparation process of a high modulus agent, comprising the following steps:

[0052] A1. Ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene are mixed in a weight ratio of 1:1:1, and added to an internal mixer for internal mixing to obtain a blend; the internal mixer speed is 100r / min, the internal mixer temperature is 220°C, and the internal mixing time is 10min. The blend is added to a twin-screw extruder for extrusion granulation to obtain a blended masterbatch; the extrusion temperature is 180°C and the extrusion time is 5min. The blended masterbatch is irradiated by a high-energy electron accelerator to obtain an irradiated blended masterbatch; wherein the irradiation voltage is 0.5MeV, the irradiation beam current density is 30mA, and the irradiation time is 20min.

[0053] A2. Mix acrylic acid and water to obtain a 30%wt acrylic acid aqueous solution; add 2mL of emulsifier SE-10 to 200mL of the acrylic acid aqueous solution, mix and stir evenly to obtain an acrylic emulsion; mix the irradiated blending masterbatch and the acrylic emulsion in a weight ratio of 1:30, then heat to 90°C and react for 12h to obtain a modified blend; then wash the modified blend with ethanol and deionized water in turn, and then add the modified blend to a 70°C oven and dry to constant weight to obtain a high modulus agent.

[0054] Example 7

[0055] This embodiment provides a preparation process of a modified wear-resistant aggregate, comprising the following steps:

[0056] Step 1: Mix siliceous and semi-siliceous refractory raw materials in a weight ratio of 1:1, add them to a ball mill and grind them to a particle size of 20-30 mm, then add them to a high-speed mixer, and set the mixing parameters as follows: the mixture temperature is 105°C. When the mixture temperature reaches the set value of 105°C, coarse aggregate is obtained.

[0057] Step 2: Grind the basalt to a particle size of 10 mm to obtain medium aggregate; mix carbide and nitride in a weight ratio of 1:1, and ball-mill to a particle size of 3 mm to obtain fine aggregate; mix coarse aggregate, medium aggregate and fine aggregate in a weight ratio of 5:60:20 to obtain wear-resistant aggregate.

[0058] Example 8

[0059] This embodiment provides a preparation process of a modified wear-resistant aggregate, comprising the following steps:

[0060] Step 1: Mix siliceous and semi-siliceous refractory raw materials in a weight ratio of 1:1, add them to a ball mill and ball-mill them to a particle size of 24 mm, then add them to a high-speed mixer, and set the mixing parameters as follows: the mixture temperature is 105°C. When the mixture temperature reaches the set value of 105°C, coarse aggregate is obtained.

[0061] Step 2: Grind the basalt to a particle size of 15 mm to obtain medium aggregate; mix carbide and nitride in a weight ratio of 1:1, and ball-mill to a particle size of 4 mm to obtain fine aggregate; mix coarse aggregate, medium aggregate and fine aggregate in a weight ratio of 7:65:25 to obtain wear-resistant aggregate.

[0062] Example 9

[0063] This embodiment provides a preparation process of a modified wear-resistant aggregate, comprising the following steps:

[0064] Step 1: Mix siliceous and semi-siliceous refractory raw materials in a weight ratio of 1:1, add them to a ball mill and grind them to a particle size of 30 mm, then add them to a high-speed mixer, and set the mixing parameters as follows: the mixture temperature is 105°C. When the mixture temperature reaches the set value of 105°C, coarse aggregate is obtained.

[0065] Step 2: Grind the basalt to a particle size of 20 mm to obtain medium aggregate; mix carbide and nitride in a weight ratio of 1:1, and ball-mill to a particle size of 5 mm to obtain fine aggregate; mix coarse aggregate, medium aggregate and fine aggregate in a weight ratio of 10:70:35 to obtain wear-resistant aggregate.

[0066] Example 10

[0067] This embodiment provides a preparation process of a high modulus asphalt structural material, comprising the following steps:

[0068] Sinopec No. 70 A-grade road petroleum asphalt was selected as the base asphalt. 5 parts of the base asphalt were put into an oven at 130°C and heated at a constant temperature until it was in a fluid state. After the temperature was constant, 1 part of the reinforced epoxy resin prepared in Example 1, 1 part of the high modulus agent prepared in Example 4 and 70 parts of the wear-resistant aggregate prepared in Example 7 were added, and shearing was performed using a low-speed shearing instrument with a shearing time of 60 minutes, a shearing temperature of 170°C and a shear rate of 3000 r / min to obtain a high modulus asphalt structural material.

[0069] Embodiment 11

[0070] This embodiment provides a preparation process of a high modulus asphalt structural material, comprising the following steps:

[0071] Sinopec No. 70A grade road petroleum asphalt was selected as the base asphalt. 8 parts of the base asphalt were put into an oven at 135°C and heated at a constant temperature until it was in a fluid state. After the temperature was constant, 3 parts of the reinforced epoxy resin prepared in Example 2, 3 parts of the high modulus agent prepared in Example 5 and 76 parts of the wear-resistant aggregate prepared in Example 8 were added, and stirred using a low-speed shear instrument with a shear time of 80 min, a shear temperature of 180°C, and a shear rate of 4000 r / min to obtain a high modulus asphalt structural material.

[0072] Example 12

[0073] This embodiment provides a preparation process of a high modulus asphalt structural material, comprising the following steps:

[0074] Sinopec No. 70A grade road petroleum asphalt was selected as the base asphalt. 10 parts of the base asphalt were put into an oven at 140°C and heated at a constant temperature until it was in a fluid state. After the temperature was constant, 5 parts of the reinforced epoxy resin prepared in Example 3, 5 parts of the high modulus agent prepared in Example 6 and 80 parts of the wear-resistant aggregate prepared in Example 9 were added, and shearing was carried out using a low-speed shear instrument with a shearing time of 90 minutes, a shearing temperature of 190°C and a shear rate of 5000 r / min to obtain a high modulus asphalt structural material.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 10 is that the reinforced epoxy resin prepared in Example 1 is not added.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 10 is that the high modulus agent prepared in Example 4 is not added.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 10 is that the wear-resistant aggregate prepared in Example 7 is not added.

[0081] Performance Testing:

[0082] According to the "Technical Specifications for Design and Construction of Rutting and Fatigue Resistant High Modulus Asphalt Mixtures" (DB37 / T3564-2019), the high modulus asphalt mixtures prepared in Examples 10-12 and Comparative Examples 1-3 were subjected to rutting and rolling tests. The test temperature of the rutting test was adjusted to 25°C, and the deformation at 45 min, the deformation at 60 min and the rutting depth were recorded in turn. Then, the test temperature of the rutting test was raised to 60°C, and the deformation at 45 min and the deformation at 60 min were recorded again.

[0083] The bending stiffness modulus of the high modulus asphalt structural materials prepared in Examples 10-12 and Comparative Examples 1-3 were tested by a small beam low temperature bending test. The test results are shown in Table 1:

[0084] Table 1

[0085]

[0086] Data Analysis:

[0087] The high modulus asphalt structural materials prepared in Examples 10-12 all have excellent anti-rutting performance, and have small deformation under different temperature conditions and for a long time; in addition, the high modulus asphalt structural materials prepared in Examples 10-12 have large bending stiffness modulus values, and the prepared modulus asphalt mixture is not prone to breakage; and the high modulus asphalt structural materials prepared are not added with reinforcing epoxy resin, high modulus agent or wear-resistant aggregate, which reduce the high and low temperature resistance, anti-rutting ability and bending stiffness modulus of the prepared high modulus asphalt structural materials to varying degrees.

[0088] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0089] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0090] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing a high modulus asphalt structural material, characterized in that: The following steps are involved: According to the weight percentage, 5-10 parts of the base asphalt are heated at a constant temperature of 130-140°C until it is in a fluid state; after the temperature is constant, 1-5 parts of the reinforcing epoxy resin, 1-5 parts of the high modulus agent and 70-80 parts of the wear-resistant aggregate are added, and sheared and stirred to obtain a high modulus asphalt structural material; The reinforced epoxy resin is prepared by the following steps: ultrasonically dispersing carbon fiber in ethanol, then adding dimethyl paraphenylene dimethyl cyanate and bisphenol A epoxy resin, mixing and stirring at 100 r / min at 60-70° C. for 0.5-1h, then adding catalyst dibutyltin dilaurate, mixing and stirring evenly to obtain a mixed system; heating the mixed system to 110-120° C., keeping the temperature for reaction for 1-2h to obtain a prepolymer; vacuum bubbling the prepolymer, and vacuum drying at 60-70° C. to constant weight to obtain a reinforced epoxy resin; The preparation process of the high modulus agent comprises the following steps: A1. Mixing ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and polytetrafluoroethylene in a weight ratio of 1:1:1, adding the mixture to a banbury mixer for mixing, and obtaining a blend; adding the mixture to a twin-screw extruder for extrusion granulation, and obtaining a blended masterbatch; and irradiating the blended masterbatch with a high-energy electron accelerator, and obtaining an irradiated blended masterbatch; A2, acrylic acid and water are mixed to obtain a 20-30%wt acrylic acid aqueous solution; an emulsifier is added to the acrylic acid aqueous solution, and the mixture is mixed and stirred to obtain an acrylic emulsion; the irradiated blended masterbatch and the acrylic emulsion are mixed, and then the mixture is heated to 80-90°C and reacted for 12 hours to obtain a modified blend; the modified blend is washed with ethanol and deionized water in turn, and then the modified blend is dried to a constant weight to obtain a high modulus agent; The wear-resistant aggregate is prepared by the following steps: Siliceous and semi-siliceous refractory raw materials are mixed and ball-milled in a weight ratio of 1:1, and mixed and stirred at a high speed to obtain a coarse aggregate with a particle size of 20-30mm; basalt is ground to obtain a medium aggregate with a particle size of 10-20mm; carbide and nitride are mixed and ball-milled in a weight ratio of 1:1 to obtain a fine aggregate with a particle size of 3-5mm; the coarse aggregate, medium aggregate and fine aggregate are evenly mixed to obtain wear-resistant aggregate.

2. The process for preparing a high modulus asphalt structural material according to claim 1, characterized in that: The usage ratio of carbon fiber, ethanol, dimethyl paraphenylene dimethyl cyanate, bisphenol A epoxy resin and dibutyltin dilaurate is 10-20g:200mL:30-40g:30-50g:0.015-0.03g.

3. The process for preparing a high modulus asphalt structural material according to claim 1, characterized in that: In step A1, the speed of the internal mixer is 50-100r / min, the temperature of the internal mixer is 200-220°C, and the mixing time is 5-10min; the extrusion temperature of the twin-screw extruder is 160-180°C, and the extrusion time is 5min; the irradiation voltage is 0.5MeV, the irradiation beam density is 15-30mA, and the irradiation time is 10-20min.

4. The process for preparing a high modulus asphalt structural material according to claim 1, characterized in that: In step A2, the emulsifier is SE-10, and the usage ratio of the acrylic acid aqueous solution and the emulsifier is 200mL:1-2mL; the weight ratio of the irradiated blended masterbatch and the acrylic emulsion is 1:20-30; and the drying temperature of the modified blend is 60-70°C.

5. The process for preparing a high modulus asphalt structural material according to claim 1, characterized in that: The silica is any one of quartz sand, vein quartz or fused quartz and their combinations; the semi-silica is any one of pyrophyllite, diatomaceous earth or silicon micropowder and their combinations; the carbide is any one of silicon carbide, boron carbide and titanium carbide and their combinations; the nitride is any one of silicon nitride, aluminum nitride and boron nitride and their combinations.

6. A high modulus asphalt structural material, characterized in that: The high modulus asphalt structural material is prepared using a preparation process for a high modulus asphalt structural material as described in any one of claims 1-5.

Citation Information

Patent Citations

  • Composite modified asphalt mixture for steel bridge and preparation method of composite modified asphalt mixture

    CN106673503A

  • High-strength high-wear-resisting cement-based material and preparation method thereof

    CN104692745A

  • High-modulus asphalt material with excellent durability and preparation method thereof

    CN112574583A